BEPS: Action 12 - Analysis of Compatibility with Brazilian and EU Fundamental Freedoms - Rasi, Beatriz de Prince (Revista de Direito Tributário Internacional Atual, 2018)
This study aims to analyse whether Action 12 of BEPS could be compatible with the fundamental freedoms of the European Union, and in addition, making a comparison with the failed attempt of implementation in Brazil in 2015, due to its incompatibility with their fundamental rights.